Upconversion Luminescence and Energy‐Transfer Mechanism of NaGd(MoO4)2: Yb3+/Er3+ Microcrystals. Issue 5 (10th February 2016) - Li, Anming; Xu, Dekang; Zhang, Yueli; Lin, Hao; Yang, Shenghong; Chen, Zhenqiang; Shao, Yuanzhi
Abstract : Uniform and well‐crystallized NaGd(MoO4 )2 : Yb 3+ /Er 3+ microcrystals with tetragonal plate morphology were synthesized by a facile hydrothermal method. The structure and phase purity of the samples were identified by powder XRD analysis. The steady‐state and transient luminescence spectra were measured and analyzed. Under 980 nm excitation, intense green luminescence at 531 and 553 nm, and red luminescence at 657 and 670 nm were observed. The optimum doping concentrations for Yb 3+ and Er 3+ are determined to be 20% and 1% in NaGd(MoO4 )2 tetragonal plate microcrystals. With increasing Yb 3+ doping concentrations, the total integral emission intensities increase first and then decrease. The red/green intensity ratio of NaGd(MoO4 )2 : Yb 3+ /Er 3+ microcrystals increases from 0.4 to 1.0 with the increase in Yb 3+ concentrations. Based on the energy level diagram, the energy‐transfer mechanisms are investigated in detail according to the double logarithmic plot of upconversion intensities versus pump powers. The energy‐transfer mechanisms for green and red upconversion luminescence are ascribed to two‐photon processes at lower Yb 3+ concentrations, and involve high‐Yb 3+ ‐induced one‐photon processes at higher Yb 3+ concentrations. For the red upconversion luminescence, energy back‐transfer process, that is, 4 S3/2 (Er 3+ ) + 2 F7/2 (Yb 3+ ) → 4 I13/2 (Er 3+ ) + 2 F5/2 (Yb 3+ ), is dominant at higher Yb 3+ concentrations. Theoretical model of the energy‐transfer mechanisms based on rate equations is established, which agrees well with the experimental results.